m6A-modified circNFIX promotes ovarian cancer progression and immune escape via activating IL-6R/JAK1/STAT3 signaling by sponging miR-647 - Wang, Ruiyu; Ye, Hui; Yang, Bowen; Ao, Mengyin; Yu, Xiuzhang; Wu, Yuke; Xi, Mingrong; Hou, Minmin (International immunopharmacology, 2023)
[Display omitted] •circNFIX was overexpressed in OC and correlated to poor prognosis.•circNFIX inhibition reduced tumor growth, metastasis and immune escape in OC.•circNFIX was activate by IGF2BPs in a m6A modification manner.•circNFIX promoted IL-6R expression via sponging miR-647.•miR-647 was negatively involved in the regulation of circNFIX in OC progression. Ovarian cancer (OC) is one of the most common gynecological malignant cancers. Our previous work confirmed that circNFIX acted as an oncogene in OC, which could promote malignant proliferation, metastasis and angiogenesis. However, the role and mechanism of circNFIX in OC immune escape remain unclear. The RNA and protein levels were determined by qRT-PCR and western blot assays. The malignant phenotypes were tested by cell count kit-8, EdU staining, flow cytometry and transwell assays. The immune cytokines levels were measured by ELISA analysis. Molecular interactions were verified employing RNA immunoprecipitation, meRIP and dual luciferase methods. In vivo validation was performed by xenograft tumor and lung metastasis model. Hematoxylin & eosin and immunohistochemistry staining were used to observe the pathological changes. The levels of circNFIX, PD-L1, and IL-6R were upregulated in OC tissues and cell lines, while miR-647 was downregulated. Functional assays showed that loss of circNFIX suppressed the growth, metastasis and immune escape of OC cells both in vitro and in vivo. On the molecular level, the m6A modification of circNFIX was elevated in OC cells, and its expression was positively correlated to m6A modification and depended on IGF2BP1 ∼ 3 recognition. Moreover, circNFIX acted as a competing endogenous RNA for miR-647 to upregulate IL-6R expression, thereby activating JAK/STAT3 signaling and elevating PD-L1 expression. Rescue assays revealed that co-silencing of miR-647 reversed the antitumor effects of circNFIX knockdown on cell proliferation, metastasis and immune escape of OC cells. This study provided a comprehensive understanding of the molecular mechanism about circNFIX in OC, demonstrating m6A activated-circNFIX accelerated OC development and immune escape via regulating miR-647/IL-6R/PD-L1 pathway.